2020
DOI: 10.1055/s-0040-1708080
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Supranuclear Palsy: A Crucial Co-occurrence in Normal Pressure Hydrocephalus or an Etiology of Hydrocephalic Presentation?

Abstract: Co-occurrences of neurodegenerative diseases in normal pressure hydrocephalus (NPH) is a remarkable topic of discussion, which has been mentioned in recent studies and it was also emphasized by the International Society for Hydrocephalus and Cerebrospinal Fluid Disorder. In this report, I illustrate two remarkable cases which were initially diagnosed with idiopathic normal pressure hydrocephalus (iNPH) and ventriculoperitoneal (VP) shunt surgery was performed, which yielded significant improvement in the clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…In our previous report [2] and in studies by several others [3], short-term recovery after shunt therapy in these patients with co-occurrent iNPH and PSP was demonstrated. Nevertheless, long-term follow-up of patients also showed that the response to shunt therapy does not persist [2,3]. However, because there is no randomized controlled trial investigating the efficiency of shunt therapy in these iNPH patients with neurodegenerative comorbidity, reliable conclusions cannot be drawn about whether CSF diversion therapy has an overall beneficial role in the pathophysiology of NPH and/or underlying neurodegenerative disease.…”
mentioning
confidence: 51%
See 1 more Smart Citation
“…In our previous report [2] and in studies by several others [3], short-term recovery after shunt therapy in these patients with co-occurrent iNPH and PSP was demonstrated. Nevertheless, long-term follow-up of patients also showed that the response to shunt therapy does not persist [2,3]. However, because there is no randomized controlled trial investigating the efficiency of shunt therapy in these iNPH patients with neurodegenerative comorbidity, reliable conclusions cannot be drawn about whether CSF diversion therapy has an overall beneficial role in the pathophysiology of NPH and/or underlying neurodegenerative disease.…”
mentioning
confidence: 51%
“…Three out of the eight PSP patients and one PD patient were reported to have responded to the CSF tap test [1]. In our previous report [2] and in studies by several others [3], short-term recovery after shunt therapy in these patients with co-occurrent iNPH and PSP was demonstrated. Nevertheless, long-term follow-up of patients also showed that the response to shunt therapy does not persist [2,3].…”
mentioning
confidence: 59%
“…Though differentiating NPH from PSP may provide more precise prediction on therapeutic prognosis, several reports have demonstrated that shunting can achieve transient response in PSP with NPH-like radiologic features. (Morariu, 1979;Magdalinou et al, 2013;Onder, 2020). Most of the additional imaging indexes require specific settings or analysis; thus, wide clinical application is limited.…”
Section: Significant Univariate Factorsmentioning
confidence: 99%